Markov processes for stochastic modeling - Ibe, Oliver C. (Oliver Chukwudi), 1947- (Elsevier insights., 2013)
Covering a wide range of areas of application of Markov processes, this second edition is revised to highlight the most important aspects as well as the most recent trends and applications of Markov processes.